2009
DOI: 10.3802/jgo.2009.20.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Premenopausal early-stage endometrial carcinoma patients with low CA-125 levels and low tumor grade may undergo ovary-saving surgery

Abstract: Objective: The purpose of this study was to determine the possible predicting factors of coexisting adnexal malignancies, and to evaluate the safety of ovary-saving surgery for early-stage endometrial carcinoma in premenopausal patients. Methods: A retrospective review of 107 patients with endometrial carcinoma who underwent surgical treatment at our institution was conducted. All patients were younger than 50 years of age and premenopausal status. Statistical analysis was performed. Results: Of the 107 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…21 Some investigators proposed their own preoperative evaluation methods including CA 125 in order to predict lymph node metastasis and extrauterine disease. [22][23][24] It is well known that MRI has a high accuracy for assessment of the depth of myometrial invasion in endometrial cancer. Many studies show that the accuracy of T2-weighted images in the determination of myometrial invasion by endometrial cancer ranges from 68 to 82% and dynamic MRI increases the accuracy up to 91%.…”
Section: Discussionmentioning
confidence: 99%
“…21 Some investigators proposed their own preoperative evaluation methods including CA 125 in order to predict lymph node metastasis and extrauterine disease. [22][23][24] It is well known that MRI has a high accuracy for assessment of the depth of myometrial invasion in endometrial cancer. Many studies show that the accuracy of T2-weighted images in the determination of myometrial invasion by endometrial cancer ranges from 68 to 82% and dynamic MRI increases the accuracy up to 91%.…”
Section: Discussionmentioning
confidence: 99%
“…59,62 In two case-control Korean studies regarding this issue, it was concluded that ovarian-saving surgery in early-stage disease did not affect disease-free survival and overall survival with a mean of 39 months follow-up 63 and recurrence. 64 They suggested young patients with a low pre-operative CA-125 and low tumor grade are considered as candidates for ovarian-saving surgery. 64 In a nationwide survey under the influence of the Korean Gynecologic Oncology Group, Lee et al 48 analyzed outcomes of 175 women undergoing ovarian-saving surgery.…”
Section: Role Of Ovarian-saving Surgerymentioning
confidence: 99%
“…64 They suggested young patients with a low pre-operative CA-125 and low tumor grade are considered as candidates for ovarian-saving surgery. 64 In a nationwide survey under the influence of the Korean Gynecologic Oncology Group, Lee et al 48 analyzed outcomes of 175 women undergoing ovarian-saving surgery. During a median follow-up of 55 months, recurrence-free survival and overall survival were 94.3% and 93.3%, respectively.…”
Section: Role Of Ovarian-saving Surgerymentioning
confidence: 99%